NOVEL SUSU DAN TELUR KARYA MIEKO KAWAKAMI TERJEMAHAN ASRI PRATIWI WULANDARI: KAJIAN FEMINISME RADIKAL - Arlilianda, Wahyu Gaesesita; Maslikatin, Titik; Umniyyah, Zahratul; Angelina, Dewi; Muhamad, Abu Bakar Ramadhan (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2024)
The topic of feminism in Japan is something that society has not yet fully accepted. This is the reason why researchers chose the novel Susu and Eggs to be used as the object of study. The discrimination that occurs against female characters in the novel leads to extreme actions and thoughts regarding women's freedom regarding their rights. Therefore, the novel Susu and Eggs is studied using radical feminism theory. The aim of this research is to describe the structural analysis and aspects of radical feminism in the object of study. Data discovery was carried out using the library study method, namely reading the novel in its entirety. The description of the data is carried out through qualitative descriptive methods. The research results show that there is a relationship between the title, theme and characterization in the novel. The title relates to the major theme which is supported by the minor theme. The theme is depicted through events that support the characters' characters. On the other hand, the aspects of radical feminism found are divided into five parts, namely: (1) women and their bodies which are related to Midoriko and Natsuko. Midoriko as a teenager who hates the nature of women, then Natsuko as a single woman who cannot find pleasure in sex, but wants to have children through a sperm donor; (2) the inequality of roles in the household which is depicted through the character Yusa Rika who hates her ex-husband; (3) women's beauty standards which include women's body shape and nipple color; (4) stereotypes about women's bodies that discuss women's instincts to get pregnant and societal stigma that prioritizes the penis over the vagina; (5) and sexual violence which includes the act of rape against the character Zen Yuriko.